Analisis Warna Pada E-Commerce Terhadap Brand Awareness - Kiristian Sibarani; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The rapid development of the internet has led to many changes about E-commerce in indonesia. The existence of E-commerce in Indonesia has started very much due to the high purchasing power of the community, with many E-commerce in Indonesia, many E-commerce owners to innovate to stay competitive. One of the innovations that is done is always to update the web appearance more attractive to the consumers, expected by updating their web display can increase brand awareness of their products. To build brand awareness to the consumer E-commerce companies create ads, banners, promotions, and improve their website. In improving their website, many aspects that need to be considered one of them is giving color. Color is one important aspect in increasing brand awareness to consumers because the color is very easy to remember by the human brain. The color display on E-commerce indirectly forms brand awareness to the brand itself, because consumers are indirectly looking at the colors that exist on the web and giving memory to the brand. This study will focus on comparing some of the colors on existing ecommerce in Indonesia, to be judged which color has a higher level of brand awareness. The conclusion of this study is the color that has a higher brand awareness to be a recommendation in giving color to E-commerce website.